Pengaruh Disiplin Kerja, Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Guru - Qodariah, Qodariah; Cintya Cintya (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to examine the effect of work discipline, work motivation, and job satisfaction on teacher performance. The research method used is descriptive quantitative, and hypothesis testing is conducted using non-parametric methods. The sampling technique employed is non-probability sampling, specifically saturated sampling, involving 64 teacher respondents. Data were collected through questionnaires using a Likert scale and analyzed using Microsoft Excel and SPSS version 26. The results indicate that work discipline and work motivation have a significant effect on the performance of public elementary school teachers in Pinang District, Tangerang City. Meanwhile, job satisfaction does not have a significant effect on teacher performance. The findings suggest that disciplined behavior and strong motivation help teachers carry out their responsibilities effectively and achieve educational objectives. This study provides empirical evidence regarding factors influencing teacher performance and offers managerial implications for school leaders in developing policies and strategies to improve productivity, commitment, and educational quality. Overall. The results may also support future research on human resource management in educational institutions nationwide and sustainably.